Enhanced binding strengths of acyclic porphyrin hosts with endohedral metallofullerenes - Grimm, Bruno; Schornbaum, Julia; Cardona, Claudia M.; Van Paauwe, John D.; Boyd, Peter D. W.; Guldi, Dirk Michael (Chemical Science, 2011)
The complementary use of spectroscopy and electrochemistry shed light onto the supramolecular interactions of calixarene scaffold bearing bisporphyrins 1 and 2 as hosts with a series of fullerenes -C , Sc N@C , and Lu N@C - as guest molecules. Importantly, the present work shows a noticeable variation in binding strength when C or endohedral fullerene guests are included into the bisporphyrins hosts. These sizeable differences could be clarified by computational models of the host-guest complexes, on the one hand, and a systematic investigation of the electron transfer chemistry, on the other hand. Detailed studies document an oxidative charge transfer (i.e., electron transfer from the bisporphyrin to the fullerene) for the C inclusion complexes, while a reductive charge transfer (i.e., electron transfer from the fullerene to porphyrin) is operative in the endohedral metallofullerene host-guest complexes. © The Royal Society of Chemistry 2011.